Studies on the Dual Cytotoxicity and Antioxidant Properties of Berberis vulgaris Extracts and Its Main Constituent Berberine. (8th January 2018) - El khalki, Lamyae; Tilaoui, Mounir; Jaafari, Abdeslam; Ait Mouse, Hassan; Zyad, Abdelmajid
Abstract : The present study attempts to investigate the cytotoxic activity of ethanol and ethyl acetate extracts of the Moroccan Berberis vulgaris and its major component berberine, together with exploring their antioxidant properties. It also consists of studying the combination effect of berberine and S-nitroso-N-acetylpenicillamine (SNAP), a nitric oxide (NO) donor, against the human breast adenocarcinoma cell line (MCF-7). Using the MTT assay, we report a differential cytotoxic effect of ethanol and ethyl acetate extracts since the ethanol extract is more cytotoxic than the ethyl acetate one, with IC50  = 3.54 μg/mL and 596.71 μg/mL, respectively. Interestingly, no cytotoxic effect was observed against normal cells. Furthermore, these extracts showed a remarkable antioxidant activity as measured by the DPPH free radicals scavenging assay. In fact, the IC50 values are 69.65 μg/mL and 77.75 μg/mL for the ethanol and ethyl acetate extracts, respectively. In addition, several concentrations of berberine, when combined with the NO donor used at IC30, induced a synergistic cytotoxic activity at concentrations ranging from 8.40 μM to 33.60 μM, as revealed by the combination index values, using the Chou–Talalay method. However, at the other concentrations tested, an antagonistic effect was observed. The observed cytotoxicity was related to apoptosis induction as demonstrated by the annexin-V-streptavidin FITC-staining analysis.